2013
DOI: 10.5402/2013/636103
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Schistosoma mansoni Infections and Associated Risk Factors among Students in Gorgora Town, Northwest Ethiopia

Abstract: Background and Objective. Schistosomiasis is highly prevalent in tropics and causes morbidity and mortality in developing countries including Ethiopia. is study is aimed to assess the current status of S. mansoni infections and associated risk factors among students in Gorgora town, Northwest Ethiopia. Method. A cross-sectional study was conducted from October 2010 to November 2010 at Gorgora, Northwest Ethiopia. All students (579) present during the study period were enrolled. Pretested questionnaires were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
28
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 17 publications
21
28
13
Order By: Relevance
“…Based on this, bathing habits, washing clothes in open water sources and crossing rivers on bare foots were independent predictors for S. mansoni infection which is similar with finding reported from Gorgora town from North Gonder [16] Saja town Northwest Ethiopia [7] …”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Based on this, bathing habits, washing clothes in open water sources and crossing rivers on bare foots were independent predictors for S. mansoni infection which is similar with finding reported from Gorgora town from North Gonder [16] Saja town Northwest Ethiopia [7] …”
Section: Discussionsupporting
confidence: 77%
“…The prevalence rate in the present study is higher than those reported 15.9% from Northern Gonder [12], 1.3% from community school of University of Gonder [18], 0.8 from Amibera District [19], 20.6% from among schooled children of Gorgora [16], 23.9% from Surbs of Mekelle city [9], 20.2% from Raya Alamata District, Northern Ethiopia [29,30], 5.95% among school children of different source users in Tigray [20], 21.2% from Southern Langano [14] , 2.1% from Jimma Zone districts surrounding Gelgel Gibe area [23] , 24% from Jimma Zone Manna District [22]. 14.4% from Brazil [31], 4.6% from Jos Nigeria [32], 12.6% from Agaie Niger state Nigeria [33], and 19.8% from Ghana [34].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Despite the promising advances in control, over 5 million Ethiopians are infected with schistosomiasis and 37.5 million more are at risk 15. Prevalence among elementary school children in Gorgora on the shores of lake Tana is 20.6% and higher at other locations throughout the country 16. The cause of this prevalence is linked to lack of research about the disease mapping and transmission, public health education, infrastructure and sanitation 15 16.…”
Section: Global Health Problem Analysismentioning
confidence: 99%